The Enterovirus Protease Inhibitor Rupintrivir Exerts Cross-Genotypic Anti-Norovirus Activity and Clears Cells from the Norovirus Replicon - Rocha-Pereira, J. (American Society for Microbiology, 2014)
Potent and safe inhibitors of norovirus replication are needed for the treatment and prophylaxis of norovirus infections. We here report that the in vitro anti-norovirus activity of the protease inhibitor rupintrivir is extended to murine noroviruses and that rupintrivir clears human cells from their Norwalk replicon after only two passages of antiviral pressure. In addition, we demonstrate that rupintrivir inhibits the human norovirus (genogroup II [GII]) protease and further explain the inhibitory effect of the molecule by means of molecular modeling on the basis of the crystal structure of the Norwalk virus protease. The combination of rupintrivir with the RNA-dependent RNA polymerase inhibitors 2′-C-methylcytidine and favipiravir (T-705) resulted in a merely additive antiviral effect. The fact that rupintrivir is active against noroviruses belonging to genogroup I (Norwalk virus), genogroup V (murine norovirus), and the recombinant 3C-like protease of a GII norovirus suggests that the drug exerts cross-genotypic anti-norovirus activity and will thus most likely be effective against the clinically relevant human norovirus strains. The design of antiviral molecules targeting the norovirus protease could be a valuable approach for the treatment and/or prophylaxis of norovirus infections.